Pendampingan Pemanfaatan Aplikasi Online sebagai Strategi Peningkatan Daya Saing Usaha Kuliner di Kedai Jajanan Zahira Surabaya - Intan Dwi Anggreini (Lembaga Pengembangan Kinerja Dosen, 2026)
The development of digital technology has encouraged micro, small, and medium enterprises (MSMEs), particularly in the culinary sector, to adapt by utilizing online applications as a strategy to increase competitiveness. This community service activity aims to improve the understanding and capabilities of business owners at Kedai Jajanan Zahira in Surabaya in utilizing online applications as a marketing and sales tool. The method used in this study is Participatory Action Research (PAR), an approach that actively involves business actors in every stage of the process. These stages include problem identification, planning, implementation, and evaluation. Data collection techniques were carried out through interviews and direct observation to obtain a realistic picture of business conditions. The results of the activity showed an increase in business owners' understanding of the importance of digitalization, improved skills in using food delivery applications and social media, and increased market reach and interaction with consumers. In addition, the use of online applications also contributed to increased operational efficiency, such as more systematic order management and transaction recording. Overall, mentoring in the use of online applications has proven effective in increasing the competitiveness of culinary businesses. This activity has a positive impact not only on increasing sales, but also on business sustainability through increased digital literacy and the ability to adapt to technological developments. Therefore, ongoing mentoring is needed so that business actors can consistently optimize the use of digital technology in developing their businesses.